The Substitution of Wheat Flour with Moringa Leaf Flour in Making Brownies with High Iron Content - Maria Saltiana Bebhe Nango; Anak Agung Ngurah Dwi Ariesta Wijaya Putra; Putu Rima Sintyadewi; I Gusti Agung Yogi Rabani RS; Ida Ayu Putu Ary Widnyani (Jurnal Pijar MIPA, 2025)
Brownies are a popular bakery product, but their nutritional profile is generally low, especially in iron content. This condition contrasts with the high prevalence of anemia among adolescent girls in Indonesia. This study aims to investigate the effect of substituting wheat flour with moringa leaf flour (Moringa oleifera) as an alternative natural fortification to increase iron levels in brownies, while also determining the optimal formulation. The method used was an experiment with a Completely Randomized Design (CRD), and data were analyzed using Analysis of Variance (ANOVA) followed by Duncan's test. The results showed that the addition of moringa leaf flour had a significant effect on increasing iron levels, as well as affecting other chemical characteristics (water, ash, protein, fat, and carbohydrate content). The best formulation was the T5K5 treatment (75% substitution of moringa leaf flour), which produced the highest iron content of 1376.58 ppm, along with a measurable macro composition (water content: 12.26%, ash: 0.94%, protein: 7.39%, fat: 20.83%, carbohydrate: 57.16%). Fundamentally, these findings imply the success of natural food fortification using local raw materials. These results are relevant for the development of functional food products as an acceptable food-based nutritional intervention strategy in addressing anemia in adolescents, as well as providing an important contribution to health education and nutritional literacy.